2005
DOI: 10.1016/j.bbrc.2005.08.070
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of PPARγ in high fat diet-induced liver steatosis in mice

Abstract: The present study was performed to examine a hypothesis that peroxisome proliferator-activated receptor gamma (PPARgamma) is implicated in high fat diet-induced liver steatosis. Mice were fed with control or high fat diet containing approximately 10% or 80% cholesterol, respectively. Macroscopic and microscopic findings demonstrated that lipid accumulation in the liver was observed as early as 2 weeks after high fat diet and that high fat diet for 12 weeks developed a fatty liver phenotype, establishing a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
248
6
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(285 citation statements)
references
References 31 publications
29
248
6
2
Order By: Relevance
“…It has been reported that PPARg is an important determinant of hepatic fat accumulation and that hepatic PPARg expression is increased in experimental models of fatty liver disease. [30][31][32] In the present study, 12-month-old TSOD mice exhibited increased hepatic mRNA levels for PPARg compared with TSNO mice of the same age. Furthermore, the hepatic staining intensity by CYP2E1 immunostaining is slightly greater in TSOD mice than in TSNO mice at both 6 and 12 months of age (Supplementary Figure 5).…”
Section: Discussionsupporting
confidence: 53%
“…It has been reported that PPARg is an important determinant of hepatic fat accumulation and that hepatic PPARg expression is increased in experimental models of fatty liver disease. [30][31][32] In the present study, 12-month-old TSOD mice exhibited increased hepatic mRNA levels for PPARg compared with TSNO mice of the same age. Furthermore, the hepatic staining intensity by CYP2E1 immunostaining is slightly greater in TSOD mice than in TSNO mice at both 6 and 12 months of age (Supplementary Figure 5).…”
Section: Discussionsupporting
confidence: 53%
“…9,10 However, the dietary fatty acid compositions were not described in these studies. In the current study, fish oil further increased PPAR␥ and target gene mRNAs, when given to mice fed high-safflower oil diet but not to mice fed high-butter diet.…”
Section: Discussionmentioning
confidence: 97%
“…6,7 C57BL/6J mice also develop fatty liver in response to an HF diet. [8][9][10] However, they are resistant to sucrose/fructose-induced fatty liver because they possess adenine Ϫ468 bp from the putative 5Ј end of the sterol regulatory element-binding protein (SREBP)-1c gene. 11 Mice with guanine at this site show increased liver SREBP-1c messenger RNA (mRNA) in response to a high-fructose diet, whereas mice with adenine do not.…”
mentioning
confidence: 99%
“…Since the expression of enzymes responsible for lipid synthesis were reduced dramatically following 3 weeks of MCDD feeding (data not shown), we speculated that the observed steatosis was the result of enhanced lipid storage. The class B scavenger receptor CD36 has been shown to facilitate the uptake of long chain fatty acids by endothelial cells as well as macrophages, and recent data suggests that this receptor plays a role in hepatic steatosis induced by feeding a high fat diet (28,29). Another member of the toll-like receptor family, TLR-2, has been shown to play a role in lipid trafficking via uptake of diacylated lipoproteins (30), a process that requires CD36 (21).…”
Section: Discussionmentioning
confidence: 99%